Multi-material direct-ink-writing of silver-based flexible and highly deformable dry electrocardiogram biopatches - Alsharif, Aljawharah A.; Aviles, Jesus M.; Zechel, Felipe M. [UNESP]; Alsharif, Nouf A.; El-Atab, Nazek (Wiley, 2024)
Of significant interest are three-dimensional (3D) printed dry electrodes, a departure from traditional wet silver/silver chloride (Ag/AgCl) electrodes. These innovative electrodes not only incorporate 3D printed personalized materials but also eliminate the need for electrolyte gel, which tends to dehydrate over time. Additionally, these electrodes boast unique attributes such as stretchability, deformability, biocompatibility, wearable comfort, and cost-effective manufacturing. While the advantages of dry electrodes are apparent, their performance optimization encounters challenges related to charge migration, particularly when scaled down to miniaturized dimensions, impacting biosignal detection. This study addresses these challenges by focusing on the development of scalable, stretchable, and highly deformable syringe-printed dry electrocardiogram (ECG) patches. The approach employs straightforward multi-material direct-ink-writing (DIW) techniques, realizing complete biopatches per print, resulting in a rapid and cost-effective fabrication process. The achieved printing resolution reaches up to 200 µm, and the conductivity of Ag/AgCl dry electrodes reaches approximately ∼ 5 × 104 S/m. This not only ensures scalability but also expands the applications of metal-based inks to various soft electronic devices, particularly in low-resource settings and environments.
Keywords: 3D printing; direct ink writing; ECG; flexible electrodes